Photodynamic therapy in combination with immune checkpoint inhibitors plus chemotherapy for first-line treatment in advanced or metastatic gastric or gastroesophageal junction cancer: A phase 2-3 clinical trial protocol - Yang Yu; Yang Yu; Rong Yu; Rong Yu; Na Wang; Na Wang; Yuping Bai; Yuping Bai; Qianling Shi; Ewetse Paul Maswikiti; Ewetse Paul Maswikiti; Hao Chen (Frontiers Media S.A., 2023)
Introduction: The immune checkpoint inhibitor (ICI) has been approved as the first-line therapy for metastatic gastric cancer in China. The treatment response of immune checkpoint inhibitor is highly dependent on the immune condition within the tumor microenvironment. Photodynamic therapy (PDT) has a long history in cancer treatment, and recent studies showed it had an immunomodulatory effect on the tumor. Here we will conduct a trial to assess whether or not a combination with Photodynamic therapy will improve the outcomes of immune checkpoint inhibitor-based treatment in patients with advanced or metastatic gastric cancer.Methods: This study is a single-center, open-label, randomized controlled, phase 2-3 trial. Patients (18-65 years old) with untreated gastric or gastroesophageal junction adenocarcinoma will be eligible for this trial. Sixty participants will be enrolled and randomly divided into the test group (n = 30) and control group (n = 30) to receive photodynamic therapy in combination with immune checkpoint inhibitor plus chemotherapy and immune checkpoint inhibitor plus chemotherapy, respectively. The primary is progression-free survival (PFS). The secondary outcomes include objective response rates (ORRs) and the occurrence of adverse events. In addition, we will also assess the changes in peripheral blood mononuclear cells (PBMCs) and tumor microenvironment after photodynamic therapy treatment in the test group. Evaluation of the tumor response will be performed every two cycles for a maximum of eight cycles.Discussion: Photodynamic therapy has an immunomodulatory effect on the tumor microenvironment; however, this has not been demonstrated for gastric cancer in a clinical trial. Based on our experience of photodynamic therapy treatment in digestive tract tumors, we plan to conduct a randomized controlled trial on this topic. This will be the first study to evaluate the synergistic effect of photodynamic therapy with immunochemotherapy for patients with advanced gastric cancer.Ethics and dissemination: It was approved by the Institutional Research Ethics Committee of Lanzhou University Second Hospital (No. 2022A-491). When this trial is completed, it will be shared at conferences and submitted for a potential publication in a peer-reviewed journal.Clinical Trial Registration:http://www.chictr.org.cn/, identifier ChiCTR2200064280.